2021
DOI: 10.3390/plants10030540
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Screening of Metabolites Profile from Romanian Tuber spp.

Abstract: Truffles are the rarest species and appreciated species of edible fungi and are well-known for their distinctive aroma and high nutrient content. However, their chemical composition largely depends on the particularities of their grown environment. Recently, various studies investigate the phytoconstituents content of different species of truffles. However, this research is still very limited for Romanian truffles. This study reports the first complete metabolites profiles identification based on gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…sinoexcavatum; however, p -cymene was reported only in T. magnatum. ,, Therefore, these two major terpenes are the first time to be reported in the selected tubers of this study. Compounds such as eucalyptol, γ-terpinene, geranyl acetone, and other terpenes were also detected in different tubers with different values.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…sinoexcavatum; however, p -cymene was reported only in T. magnatum. ,, Therefore, these two major terpenes are the first time to be reported in the selected tubers of this study. Compounds such as eucalyptol, γ-terpinene, geranyl acetone, and other terpenes were also detected in different tubers with different values.…”
Section: Resultsmentioning
confidence: 64%
“…9,10,12 The properties of the soil, the surrounding environment, and particularly the host trees have a significant impact on the chemical makeup of truffles. 2 Recent studies have used various methodologies, mainly HS-SPME-GC−MS, to analyze the volatile components of different truffle species. 5 When the volatile compounds of truffles were analyzed at the level of the compound class, it was frequently found that alcohols, aldehydes, ketones, acids, esters, terpenes, and sulfur compounds were detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, different sample masses (100–500 mg), extraction time spans (15–45 min) and extraction temperatures (30–50°C) were investigated using bulk samples. During optimization the signals of representative compounds belonging to different compound classes (i.e, 2-butanol, 2-butanone, 4-hydroxy-3-hexanone and 1-octen-3-ol) were monitored ( 1 , 5 , 7 ). The peak areas obtained under the individual conditions were normalized with regard to the peak area obtained for each compound under the optimum/selected conditions, and were expressed as percentage.…”
Section: Methodsmentioning
confidence: 99%
“…The main steps of this technique include: (a) partitioning of analytes between the matrix and the extraction phase, and (b) subsequent desorption of the concentrated analytes into the analytical instrument in a single step ( 14 16 ). Head-space solid phase microextraction combined to GC-MS has been used to assess the volatile fingerprint of several truffle species ( 2 , 7 , 13 , 17 , 18 ). The majority of the studies report the volatiles identified for different analyzed species, and the use of chemometric tools to enhance the conclusions derived from the experimental data and reveal characteristic markers is limited ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%